Reações adversas a antibióticos em crianças hospitalizadas – uma revisão sistemática - Santana, Vanessa Lima de (2018)
Introduction: Adverse drug reactions (ADRs) worldwide are a public health problem, with the pediatric population being the most affected. In addition, one of the pharmacological classes most frequently related to ADR is antibiotics. However, studies that evaluate the incidence of ADR for a single class of medications are still scarce. Objective: To analyze the profile of adverse reactions to antibiotics in hospitalized pediatric patients. Methods: A systematic review of the literature was carried out to analyze the incidence of ADR in children using antibiotics according to the following steps: (1) identification of studies in the following databases: Embase / PubMed, LILACS, Web of Science and COCHRANE, using the descriptors "adverse reaction to drugs", "children", "hospital" and "antibiotic". (2) evaluation of studies, in which the title, abstract and full text were evaluated, according to the pre-established inclusion criteria. The variables analyzed were incidence, type of severity of adverse reactions to antibiotics and what instrument was used to evaluate the causality of these reactions. Results: Of the 11 studies included in this review, we observed an incidence rate of adverse reactions (47%) for patients using amoxicillin associated with potassium clavulanate. The types of ADR associated with this incidence were: gastrointestinal problems, rashes and fever. Only one included article reported using the World Health Organization and Uppsala Monitoring Center criteria for classification and confirmation of adverse reactions through causality. Conclusion: In view of the above, with previous studies, the importance of using validated instruments to assess the cause of adverse reactions in evidence-based health practice, and the incidence of adverse reactions to antibiotics, helps in the clinical setting increasing patient safety.